1994
DOI: 10.1111/j.1467-8624.1994.tb00760.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Health Knowledge in Low-Income Mexican-American Children

Abstract: Children growing up in poverty are at risk for various health problems. For low‐income, Mexican‐American children, these risks include obesity, diabetes, and accidental injuries, 3 conditions that can largely be prevented by healthy life‐styles. Despite the potential for prevention through education leading to health‐promoting behaviors, very little is known about the development of health knowledge in this population. The present study examined low‐income, Mexican‐American children's understanding of the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The few studies that included young children's perceptions regarding variables associated with healthy weight suggest that by age 3 most children have the cognitive ability to form rudimentary health concepts based on their life experiences (Mobley 1996). Nutrition knowledge lags behind health issues such as safety and hygiene (Olvera‐Ezzell et al . 1994), but is better developed than understanding of how physical activity benefits health (Lasky & Eichelberger 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that included young children's perceptions regarding variables associated with healthy weight suggest that by age 3 most children have the cognitive ability to form rudimentary health concepts based on their life experiences (Mobley 1996). Nutrition knowledge lags behind health issues such as safety and hygiene (Olvera‐Ezzell et al . 1994), but is better developed than understanding of how physical activity benefits health (Lasky & Eichelberger 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The health socialization literature identifies a range of parental socialization messages that have enduring effects on child health behaviors, including the transmission of knowledge/information, direct control of children's behaviors (e.g., eating), reinforcing or discouraging child behavior via parental responses, parental modeling, and managing external influences (e.g., exposure to certain foods; Baranowski, 1990). Culture uniquely shapes parental messages on health; for example, compared with European American mothers, mothers of Mexican origin were more likely to emphasize socialization messages on hygiene and safety than nutrition (Lees & Tinsley, 2000; Olvera‐Ezzell et al, 1994). Diep et al (2017) found that Chinese American parents influenced their children's eating behaviors and preferences for Chinese food through modeling, affecting the access or availability of foods, or restricting unhealthy foods.…”
Section: Introductionmentioning
confidence: 99%